Determinan Niat dan Ide Bunuh Diri Pada Remaja Menurut Theory of Planned Behavior (TPB); Studi Literatur Tahun 2021-2025 - Siti Naila Sya’bani; Luqman Effendi (Jurnal Ventilator, 2025)
Suicide among adolescents is a serious mental health problem; however, not all adolescents with suicidal ideation progress to suicide attempts. Understanding the psychological factors that influence the transition from intention to actual behavior is essential for effective prevention efforts. This study aims to examine the role of the Theory of Planned Behavior (TPB) in understanding the transition from suicidal intention to suicide attempt behavior, as well as protective behaviors such as mental health help-seeking among adolescents. This study employs a literature review method with a quantitative correlational approach based on the TPB framework, using secondary data from scientific articles published between 2021 and 2025 and obtained through Google Scholar and PubMed. The findings indicate that suicidal ideation is the strongest predictor of suicidal intention but does not always lead to suicide attempts. TPB constructs, particularly perceived behavioral control (PBC), play a crucial role in determining whether intention develops into risky behavior or is redirected toward protective behaviors. In addition, positive attitudes toward mental health services and supportive social norms were found to strengthen adolescents’ intentions to seek help. In conclusion, TPB is a relevant theoretical framework for explaining both risk pathways and prevention pathways of adolescent suicide and has the potential to serve as a foundation for developing more effective prevention interventions.